COMPARISON OF LATERAL INTERNAL SPHINCTEROTOMY WITH 0.2% GLYCERYL TRINITRATE IN THE MANAGEMENT OF CHRONIC ANAL FISSURE - Rehman, Habib Ur; Pervez, Mohammad (Pakistan Armed Forces Medical Journal, 2011)
Objective: To compare the effectiveness of topical Glyceryl trinitrate Ointment with Lateral internal Sphincterotomy in terms of relief of pain, healing of fissure and absence of bleeding over a period of two months. Study Design: Randomized controlled trial. Place and Duration of Study: Department of Surgery, Combined Military Hospital Peshawar from Feb 2007 to August 2007. Patients and Methods: This study included 80 patients of chronic anal fissure. Patients were randomly divided in two groups with 40 patients in each group. One group was prescribed with 0.2% GTN Ointment intra-anally 4 times a day for 8 weeks in OPD (groupA). Second group was admitted in Surgical ward and lateral internal sphincterotomy was performed on each patient by open technique under general anaesthesia (groupB). Results: In Group A 33 (82.5%) patients had healed fissure at the end of 8 weeks, While in group B, 37 out of 40 (92.5%) patients had healed fissure at the end of 8 weeks. Conclusion: 0.2% Glyceryl trinitrate can be offered as first line of treatment for chronic anal fissure which means that surgery can be avoided in more than 82% of the patients.